A Fast Estimation of Activation Energy of Low Density Polyethylene (LDPE) - Jassim, Widad H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A dynamic experimental study of thermal decomposition of low density polyethylene has been carried out with two different heating rates  .As usual , we can determine the activation energy of any polymer using( 3 - 6 ) TGA experiment as minimum , but  in  this work , we estimate the activation energy of  LDPE  using two of  TGA  experiments only